Its Use In Ensuring Intervention And Family Stability In Social Work - Kayumov Kakhramon Nozimjonovich; Toshpolatov Dostonjon Nodirjon ugli; Abudvalieva Mumtozxon Asilbekovna (Zien Journals, 2023)
This article focuses on the importance of intervention in social work in ensuring the family and its formation, development, and stability. The article also covers the issues of Family Policy and the reforms that Uzbekistan is implementing to ensure family strength. At the same time as a result of these reforms, the issue of interventions affecting family strength has been analyzed.
Keywords: intervention; Social Work; Social Work officer